Selective cyclooxygenase-2 silencing mediated by engineered E. coli and RNA interference induces anti-tumour effects in human colon cancer cells - Strillacci, A (Nature Publishing Group, 2010)
BACKGROUND: Cyclooxygenase-2 (COX-2) overexpression is strongly associated with colorectal tumourigenesis. It has been demonstrated that the chronic use of non-steroidal anti-inflammatory drugs (COX inhibitors) partially protects patients from colorectal cancer (CRC) development and progression but induces severe cardiovascular side effects. New strategies for selective COX-2 blockade are required. METHODS: We developed an improved technique, based on RNA interference (RNAi), to gain a selective COX-2 silencing in CRC cells by a tumour-dependent expression of anti-COX-2 short-hairpin RNA (shCOX-2). Anti-COX-2 shRNA-expressing vectors were delivered in CRC cells (in vitro) and in colon tissues (ex vivo) using engineered Escherichia coli strains, capable of invading tumour cells (InvColi). RESULTS: A highly tumour-dependent shCOX-2 expression and a significant COX-2 silencing were observed in CRC cells following InvColi strain infection. Cyclooxygenase-2 silencing was associated with a strong reduction in both proliferative and invasive behaviour of tumour cells. We also demonstrated a pivotal role of COX-2 overexpression for the survival of CRC cells after bacterial infection. Moreover, COX-2 silencing was achieved ex vivo by infecting colon tissue samples with InvColi strains, leading to anti-inflammatory and anti-tumour effects. CONCLUSION: Our RNAi/InvColi-mediated approach offers a promising tool for a highly selective COX-2 blockade in vitro and in vivo.